Estimasi hasil tangkapan maksimum ekonomi sumberdaya ikan pelagis di perairan Laut Kabupaten Tojo Una-Una, Indonesia - Alimudin Laapo; Dafina Howara; Marhawati Mappatoba (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2020)
The marine area of Tojo Una-Una District has the potential for fishery resources and small islands resources which are used for fishery activities and marine ecotourism. Although most of its territorial waters are a conservation area of the Togean Islands National Park (TINP), in the utilization of fish resources in this area, some still use destructive tools that threaten the habitat and preserve of pelagic fish resources and the economic sustainability of local communities. This study aims to estimate the maximum economic potential of the catch and the level of utilization of pelagic fish resources in Tojo Una-Una districts sea waters. The research data used combines time-series data from pelagic fish catches and fishing effort (trips) from 2003 to 2015, field survey data, and analyzed using the Gordon-Schaefer Bioeconomic Model approach or the Surplus Production Model. The estimation results show that the total maximum economic Yield (MEY) of pelagic fish resources in the waters of Tojo Una-Una District is quite large, namely 14,950.54 tons per year. Although the potential level of economic utilization of large pelagic fish resources is higher than the use of small pelagic fish, the potential economic rent obtained from the use of small pelagic fish is still higher than that of large pelagic fish. Given that the utilization of pelagic fish resources in the waters of Tojo Una-Una District is under MEY, a careful addition to the capacity of the fishing effort is needed to increase the economic benefits of fish resources for fishermen and the region.Keywords:Estimation,Maximum Economic Yield Pelagic FishABSTRAKWilayah perairan laut Kabupaten Tojo Una-Una memiliki potensi sumberdaya perikanan dan sumberdaya pulau-pulau kecil yang dimanfaatkan untuk kegiatan perikanan dan ekowisata bahari. Wilayah perairan Kabupaten Tojo Una-Una sebagian besar merupakan kawasan konservasi Taman Nasional Kepulauan Togean (TNKT), namun dalam pemanfaatan sumberdaya ikan di wilayah ini masih ada yang menggunakan alat yang sifatnya destruktif sehingga mengancam habitat, kelestarian sumberdaya ikan pelagis dan keberlanjutan ekonomi masyarakat lokal. Penelitian ini bertujuan untuk mengestimasi potensi ekonomi maksimum hasil tangkapan dan tingkat pemanfaatan sumberdaya ikan pelagis di perairan laut kabupaten Tojo Una-Una. Analisis data dilakukan dengan menggabungkan data time-series hasil tangkapan ikan pelagis dan upaya tangkap (trip) dari tahun 2003 hingga 2015. Data survei lapangan dianalisis dengan menggunakan pendekatan Model Bioekonomi Gordon-Schaefer atau Model Produksi Surplus. Hasil analisis menunjukkan bahwa total tangkapan maksimum ekonomi (MEY) sumberdaya ikan pelagis di perairan Kabupaten Tojo Una-Una mencapai 14.950,54 ton per tahun. Namun demikian, potensi tingkat pemanfaatan secara ekonomi sumberdaya ikan pelagis besar lebih tinggi dibanding pemanfaatan ikan pelagis kecil, meskipun potensi rente ekonomi yang diperoleh dari pemanfaatan ikan pelagis kecil masih lebih tinggi dibanding ikan pelagis besar. Kesimpulannya, pemanfaatan sumberdaya ikan pelagis di wilayah perairan Kabupaten Tojo Una-Una berada di bawah MEY, maka penambahan secara hati-hati kapasitas upaya tangkap diperlukan untuk meningkatkan manfaat ekonomi sumberdaya ikan bagi nelayan dan daerah.Kata kunci:Estimasi,Hasil ekonomi maksimum,Ikan Pelagis